Radiocarbon measurements reveal underestimated fossil CH4 and CO2 emissions in London - Zazzeri, Giulia; Graven, Heather; Xu, Xiaomei; Saboya, Eric; Blyth, Liam; Manning, Alistair J.; Chawner, Hannah; Wu, Dien; Hammer, Samuel (Geophysical research letters, 2023)
Radiocarbon (14C) is a powerful tracer of fossil emissions because fossil fuels are entirely depleted in 14C, but observations of 14CO2 and especially 14CH4 in urban regions are sparse. We present the first observations of 14C in both methane (CH4) and carbon dioxide (CO2) in an urban area (London) using a recently developed sampling system. We find that the fossil fraction of CH4 and the atmospheric concentration of fossil CO2 are consistently higher than simulated values using the atmospheric dispersion model NAME coupled with emission inventories. ...
Online veröffentlicht am 27. Juli 2023
Im Titel erscheinen die Ziffern "4" und "2" tiefgestellt
Gesehen am 12.12.2023